Are Remittances Insurance? - Yang, Dean; Choi, HwaJung (World Bank, 2012)
A basic theoretical result is that if there is a Pareto-efficient allocation of risk across individual entities (in this case, individual household members) in a risk-sharing arrangement, individual consumption should not be affected by idiosyncratic income shocks. Data and Sample Construction The empirical analysis uses data from linked household surveys conducted by the Philippine National Statistics Office covering a nationally representative household sample: the Labor Force Survey, the Survey on Overseas Filipinos, the Family Income and Expenditure Survey, and the Annual Poverty Indicators Survey. The variables included in the vector of controls, Wh, are a set of household characteristics in the first period (January June 1997): an indicator for urban location; five indicators for the household head's highest level of education completed (elementary, some high school, high school, some college, and college or more; less than elementary omitted); six indicators for head's occupation ( professional, clerical, service, production, other, not working; agricultural omitted); and log per capita household For example, a need to accumulate resources for a large household purchase (such as a vehicle) or some other lump-sum payment (tuition, medical expenses) might lead to both increased remittances, increased domestic labor supply, and increased domestic income. Table 4 presents the results from OLS and instrumental variable regressions where the outcome variable is the change in household expenditures between the January June 1997 and April September 1998 reporting periods, expressed as a share of initial (January June 1997) household expenditures. This may reflect the fact that international migration requires fixed up-front costs (such as fees to recruitment agencies), so that households facing credit and savings constraints become more willing or able to pay the fixed costs when current income increases. Impact of Domestic Income Shock on All Outcomes, 1997 98: Fixed Effect OLS and Instrumental Variable Estimates, Controlling for Exchange Rate Shock, Migrant Households Only Migrant households Ordinary least squares 20.080* (0.042) 0.500*** (0.071) 20.032 (0.021) Instrumental variable 20.639** (0.219) 0.256 (0.169) 20.107 (0.176) Outcome Total remittance Total expenditure Overseas worker indicator Number of observations 1,655 1,655 *Significant at 10 percent level; **Significant at 5 percent level A key question is whether remittance responses to income shocks depend on the performance or availability of alternative methods of coping with risk, such as asset sales, credit markets, and reciprocal transfer networks. One reason for the finding of such large responses of remittances to rainfall-driven income shocks could be that such shared shocks make it more difficult to access credit or interhousehold assistance networks that normally help households cope with risk. Policies to facilitate remittances include strengthening financial infrastructure and payment systems to lower the cost and broaden the reach of formal remittance channels.